El registro de Lestodelphys Tate, 1934 (Didelphimorphia, Didelphidae) en el Pleistoceno tardío del noreste de la Provincia de Buenos Aires, Argentina - Martinelli, A. G. (2013)
New records of Lestodelphys sp. (Marsupialia: Didelphimorphia: Didelphinae: Thylamyini) were found at the base of Eloisa Member, Río Luján Formation (late Pleistocene) from three sites located on the right bank of the Río Reconquista, Merlo County, northeast Buenos Aires Province (Argentina). The records of these specimens are among the northernmost for Lestodelphys from the Pleistocene of Buenos Aires Province. The material consists of four lower hemimandibles. They have a combination of features suggesting either: (1) a high morphological variability in the fossil species L. juga, in which case the current diagnosis of this taxon has to be reviewed; or (2) that the validity of L. juga must no longer be considered, as already stated by previous researchers. The occurrence of Lestodelphys is used as an environmental indicator because the current species is confined to areas of arid to semiarid conditions. The presence of the new specimens in the Pleistocene of Merlo reinforces previous paleo-environmental inferences for the levels of provenance.